Alkane Carbon‐Hydrogen Bond Functionalization as a Tool Toward a Steric Parameter for Hydrotris(pyrazolyl)borate (Tpx) Ligands. Issue 10 (18th October 2017) - Caballero, Ana; Pérez, Pedro J.
Abstract: The effect of a series of hydrotris(pyrazolyl)borate ligands (Tp x ) in the regioselectivity of the catalytic functionalization of the secondary carbon‐hydrogen bonds of hexane with ethyl diazoacetate and Tp x CuL as the catalysts has led to the definition of the relative steric parameter SPR . The validity of the parameter has been assessed upon its correlation with the regioselectivity observed in several transformations (olefin cyclopropanation, C−H functionalization, C−H amidation), in all cases a good degree of fitting being observed. Abstract :